1988
DOI: 10.1099/0022-1317-69-10-2595
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Herpes Simplex Virus Type 1 Trans-inducing Factor Vmw65

Abstract: SUMMARYThe herpes simplex virus type 1 (HSV-1) polypeptide Vmw65 is a structural component of the virus particle and is also responsible for trans-induction of immediate early (IE) transcription. Functional domains of this polypeptide were investigated by constructing a series of 10 plasmids each with a 12 bp insertion in the gene encoding Vmw65. Plasmids were analysed for their ability to stimulate IE transcription in short term transfection assays, and the altered Vmw65 polypeptides were assayed for the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 30 publications
4
102
0
Order By: Relevance
“…The structures of the four mutant VP16 proteins are shown in Figure 2, which also summarizes the results of these experiments. Previous mutagenesis studies (Ace et al 1988;Werstuck and Capone 1989a, b;O'Hare 1989, 1990) have identified two important regions for VP 16-induced complex formation; we refer to these as region I (amino acids 173-241) and region II (amino acids 317-403). We constructed two mutants, RI-A and RII-A, in which regions I and II are deleted individually.…”
Section: Vp16 Mutations Affecting Hcf Dna and Oct-i In Teractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of the four mutant VP16 proteins are shown in Figure 2, which also summarizes the results of these experiments. Previous mutagenesis studies (Ace et al 1988;Werstuck and Capone 1989a, b;O'Hare 1989, 1990) have identified two important regions for VP 16-induced complex formation; we refer to these as region I (amino acids 173-241) and region II (amino acids 317-403). We constructed two mutants, RI-A and RII-A, in which regions I and II are deleted individually.…”
Section: Vp16 Mutations Affecting Hcf Dna and Oct-i In Teractionsmentioning
confidence: 99%
“…We constructed two mutants, RI-A and RII-A, in which regions I and II are deleted individually. We also assayed the activities of two previously characterized 4-amino-acid insertion mutants, in9 and inl4 (Ace et al 1988), which we refer to here simply as RI-i and RII-i, respectively. These two mutations disrupt formation of the HCF-dependent VP16-induced complex; the RII-i mutant, however, can still participate in virion assembly, suggesting that its structure is not grossly altered (Ace et al 1988).…”
Section: Vp16 Mutations Affecting Hcf Dna and Oct-i In Teractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The probe was a radiolabelled 1.6 kbp HindlII/EcoRI fragment from pMC 17 (Ace et al, 1988), containing the coding sequences for Vmw65.…”
Section: Cells and Viruses Hfl (Flow 2002) Cells Were Obtained From mentioning
confidence: 99%
“…VP16 is a modular protein and contains separable domains that are important for complex formation and transactivation (19,(23)(24)(25)(26)(27)(28)(29). The carboxyl-terminal acidic activation domain is essential for transcriptional activation but not for complex assembly.…”
mentioning
confidence: 99%